Studi Kasus Penerjemahan Dokumen Kesehatan dan Keselamatan Kerja di Industri Manufaktur - Kurnia Prayogi; M Afifulloh; Widyasari Widyasari (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2025)
Based on the background of the title I took, and I am an employee at one of the manufacturing companies in Batam. Therefore, I raised the title about translating Occupational Health and Safety documents in order to provide a breakthrough for employees to understand and comprehend, even though they do not fully understand foreign languages, especially English, so that there is no misunderstanding of communication that has fatal consequences for employees and the company where we work. Rojak and Handayani (2023) stated that language barriers in translating Occupational Health and Safety (OHS) technical documents can affect the effectiveness of safety communication in the workplace. This study aims to analyze the level of accuracy of translating Occupational Health and Safety (OHS) terms from English to Indonesian in the manufacturing industry based on a literature review of 15 recent journals, where the results of this study explain that incompatibility or dissimilarity in translation has the potential to cause miscommunication that is very dangerous to the safety of employees and employees in a company. The research that I did is not solely for employees and employees in the company where I work, but for all employees and employees wherever they work, especially in the manufacturing industry. The definition of manufacturing industry is a company or industrial body that processes raw materials into products or semi-finished materials and from semi-finished materials into products, which processing can be done mechanically or chemically.